(untitled) (Research, Society and Development, 2022)
Recognizing the importance of nursing professionals and the risk of mental illness in a pandemic, this study aimed to determine the scientific results of the impact of the pandemic on the mental health of nursing teams and coping strategies. The methodology used was an integrative literature review (RIL). Structured data collection was performed through lilacs, scans and pubmed. The inclusion criteria were: all articles published in Portuguese and English, according to the aforementioned descriptors, within the timeline of the last two years (2020-2022), free of charge. Monographs, essays, review articles, case reports and experiences, notes and editorials are excluded. For the classification of methodological quality, observational studies were evaluated using axis tool; The selected articles bring to light a series of factors that directly impact the mental health of nursing professionals who are at the forefront of combating COVID-19, dealing daily with difficult situations, such as patient deaths, lack of personal protections for the use of material resources, complexity of disease severity, new protocols, and larger workloads. Therefore, it should be emphasized that the lack of adequate conditions in the work environment directly affects the mental health of nursing professionals. It can be concluded that nursing professionals who struggle on the front line during the COVID-19 pandemic, in the face of high daily mortality rates, are in the mental overload phase due to worry, overwork, anxiety and depression and prolonged shifts of work. With this, these professionals who are going through this pandemic are more likely to suffer from psychological problems such as depression.